1988
DOI: 10.1073/pnas.85.9.2924
|View full text |Cite
|
Sign up to set email alerts
|

myc protooncogene linked to retroviral promoter, but not to enhancer, transforms embryo cells.

Abstract: To define conditions under which the chicken protooncogene p-myc is converted to a viral and possibly to a cellular transforming gene, we assayed transforming function of hybrid genes put together from cloned retroviral and p-myc elements and of p-myc genes isolated from spontaneous viral lymphomas. Transforming function was measured in quail embryo cells transfected with cloned myc genes. We found that only myc genes with a promoter of a retroviral long terminal repeat (LTR) located between the native p-myc p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…These experiments confirm and extend studies with other proto-onc genes, which have demonstrated that about 100-fold increased expression from retrovirus promoters is sufficient for transforming function of diploid cells and tumorigenicity. Examples include retrovirus-promoted coding regions of proto-ras (3,16,18,20,21) and proto-myc (17,19,29). Thus, our experiments support the hypothesis that retroviral onc genes derive transforming function from strong viral promoters rather than from mutations that affect the coding sequence of native proto-onc genes (2,11).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These experiments confirm and extend studies with other proto-onc genes, which have demonstrated that about 100-fold increased expression from retrovirus promoters is sufficient for transforming function of diploid cells and tumorigenicity. Examples include retrovirus-promoted coding regions of proto-ras (3,16,18,20,21) and proto-myc (17,19,29). Thus, our experiments support the hypothesis that retroviral onc genes derive transforming function from strong viral promoters rather than from mutations that affect the coding sequence of native proto-onc genes (2,11).…”
Section: Discussionsupporting
confidence: 73%
“…However, transforming function of typical retroviral onc genes, including src, myc, and ras genes, was recently shown to depend on retroviral promoters rather than on the mutations that set apart the coding regions of viral and proto-onc genes (3,(16)(17)(18)(19)(20)(21). These promoters increase expression about 100-fold compared to the corresponding proto-onc genes (11,21,22).…”
mentioning
confidence: 99%
“…Activation of the proto-one genes, for example the p-myc, happens when the provirus integrates between the native p-myc promoter and the second exon of the p-myc as already mentioned (Zhou and Duesberg, 1988).…”
mentioning
confidence: 98%
“…generate recombinant genes capable of transforming diploid cells (Zhou and Duesberg, 1988;Onions et al, 1987). Such genes may be cellular cancer genes.…”
mentioning
confidence: 99%
See 1 more Smart Citation